When An Apology Implicates A Doctor: Legal Consideration - Tan, Choon Yong Alex (Malaysian Journal of Medical Sciences, 2025)
In recent years, the increasing volume of medical negligence in Malaysia has highlighted crucial concerns regarding the standard of care, informed consent, and liability within the healthcare system. If left unchecked, the rising compensation awards will inevitably affect consumers, namely, the community. Various means exist to potentially prevent litigation, such as engaging in alternative dispute resolution, which includes seeking a sincere apology from the doctor. However, in the judicial system, apologising to patients may also convey the admission of liability, which holds the doctor responsible for negligence. Currently, there is no specific legal framework governing the consequences of apologies in medical error cases. The outcome often depends entirely on the judicial interpretation.